Digitalisasi Pembelajaran Sekolah Berbasis Pesantren di SMK Hasyim Asy’ari - Lailatus Shajidah; Arni Yuniar Prastika; Muhitotun Nadhifah; Icha Deshira Fitrianni; Angger Satrio Agung Jayadipa; Ahmad Taufiq (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
The implementation of digitalization of learning at SMK Hasyim Asy'ari has proven to be effective in improving the quality of education. Online platforms like Kejar.id make it easy to access materials, improve student comprehension, and encourage active interaction. The integration of multimedia and learning videos proved to be interesting and effective, with an increase in academic grades by up to 20%. While there are challenges such as technology access gaps, collaborative efforts can overcome them. The integration of pesantren values in digital learning is important to shape the character of students. The holistic model of SMK Hasyim Asy'ari can be an inspiration for other schools. This research opens up opportunities to study the long-term impact of digitalization of learning on academic achievement, social development, and student character. Digitalization of learning in pesantren-based schools has great potential to create a generation that is ready to face the future.